The Interplay of Subjective Quality Evaluation, Prototyping Technologies and the User's Technology Acceptance. (May 2022) - Buker, T.; Endress, F.; Miehling, J.; Wartzack, S.
Abstract: Subjective product quality is a fundamental aspect to maintain a high level of user acceptance and to provide a good user experience. Prototypes can be used to evaluate subjective product quality in early design phases. We conducted an empirical study to examine the influence of different (re)presentations of prototypes determined by the chosen technology (2D image, VR, AR, 3D print) and the user's technology acceptance. Based on the results we recommend 2D images as most reliable for evaluating subjective product quality.